Self-assembled amphiphilic mixed α/β-tetrapeptoid nanostructures as promising drug delivery vehicles. (17th February 2017) - Goel, Rahul; Sharma, Ashwani Kumar; Gupta, Alka
Abstract : Tetrapeptoid nanostructures have been prepared and their potential used for delivering hydrophobic drug molecules. Abstract : We are currently investigating self-assembled nanostructures from short oligomers of β-amino acids and their subsequent use as drug delivery systems. Successful demonstration by our group of self-assembled nanovesicular structures, generated from a β-alanine homotetramer, as carriers for the hydrophobic drugl -Dopa has prompted us to design even more efficient drug delivery systems from the β-amino acid containing peptoid. In the present study, we report a systematic study on the self-assembly of an amphiphilic mixed α/β-tetrapeptoid, H-βAla-βAla-Lys-βAla-NH2 . The secondary structure of the tetrapeptoid in a self-assembled state is studied using Fourier Transform Infrared (FTIR) spectroscopy, and Circular Dichroism (CD). These studies are strongly indicative of the presence of the β-sheet conformation, a requisite for self-assembly. Dynamic Light Scattering (DLS) measurements reveal that the tetrapeptoid self-assembles to stable nanovesicular structures having an average hydrodynamic size of ∼343 nm and a zeta potential of ∼21 mV. The morphology of the self-assembled cationic structures in aqueous solutions was studied by Transmission Electron Microscopy (TEM). Supportive evidence regarding the conformation of the peptoid is provided by a conformational search using computational methods. The theoretically predicted minimum energy structure depicts a curved strand type of conformation. Four of these curved strands are then subjected to a geometry optimization that resulted in the formation of an assembly with a hydrophobic core and a hydrophilic exterior. Successful entrapping of hydrophobic molecules of drugs, aspirin andl -Dopa, into the generated nanostructures is revealed by DLS measurements and TEM micrographs. Absorption spectroscopic studies were conducted to study the interaction between the generated nanostructures and each of the hydrophobic drugs, aspirin, andl -Dopa with significant association constant values of the order of 10 6 to 10 5, respectively. These described nanostructures from the tetrapeptoid may be developed into efficient drug delivery systems.